2017
DOI: 10.1159/000481463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnesium on Glomerular Filtration Rate and Recovery of Hypertension in Women with Severe Preeclampsia

Abstract: Introduction: Magnesium sulfate is used for preventing seizures in patients with severe preeclampsia. Previous studies have demonstrated that magnesium plays a significant role in the endothelial function and might have clinically beneficial vasodilating properties. Objectives: This study is aimed at evaluating the effect of magnesium sulfate on the glomerular filtration rate (GFR) during the first 24 h after delivery and during the duration of recovery from hypertension in preeclampsia. Methods: Severe preecl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
0
13
0
3
Order By: Relevance
“…It has long been known that magnesium deficiency causes an increased incidence of cardiovascular diseases, including hypertension and atherosclerosis ( Saris et al, 2000 ; Seelig, 1994 ). As mentioned above, magnesium has a good effect on hypertension during pregnancy ( Alexander et al, 2006 ; Kreepala et al, 2018 ). Oral magnesium supplementation (300 mg/kg magnesium oxide daily) for 1 month effectively decreases systolic, diastolic and mean arterial blood pressure in patients with essential hypertension at home ( Banjanin and Belojevic, 2018 ).…”
Section: Therapeutic Application Of Magnesium In Other Diseasesmentioning
confidence: 97%
See 1 more Smart Citation
“…It has long been known that magnesium deficiency causes an increased incidence of cardiovascular diseases, including hypertension and atherosclerosis ( Saris et al, 2000 ; Seelig, 1994 ). As mentioned above, magnesium has a good effect on hypertension during pregnancy ( Alexander et al, 2006 ; Kreepala et al, 2018 ). Oral magnesium supplementation (300 mg/kg magnesium oxide daily) for 1 month effectively decreases systolic, diastolic and mean arterial blood pressure in patients with essential hypertension at home ( Banjanin and Belojevic, 2018 ).…”
Section: Therapeutic Application Of Magnesium In Other Diseasesmentioning
confidence: 97%
“…Magnesium can inhibit the release of acetylcholine from motor nerve endings, block nerve-muscle conduction, and relax skeletal muscle. Therefore, it effectively controls and prevents preterm labor, gestational hypertension, preeclampsia, and eclampsia with few side effects on the fetus ( Alexander et al, 2006 ; Kreepala et al, 2018 ; Magee and von Dadelszen, 2018 ). Clinically, magnesium sulfate is utilized for fetal neuroprotection in preterm birth ( Bachnas et al, 2019 ; Rouse et al, 2008 ).…”
Section: Therapeutic Application Of Magnesium In Other Diseasesmentioning
confidence: 99%
“…Recent study has shown that the physiological decrease of magnesium during pregnancy is associated with endothelial dysfunction. Which could potentially mark as a factor that leads to preeclampsia [ 19 ]. Several literatures have demonstrated that early preeclampsia can be predicted by biomarkers such as serum placental growth factor (PIGF), soluble fms-like tyrosine kinase 1 and soluble endoglin [ 20–22 ].…”
Section: Introductionmentioning
confidence: 99%
“…La restricción de líquidos en el puerperio, junto con la administración de diuréticos, puede considerarse apropiada en circunstancias específicas. Este tratamiento también puede disminuir el riesgo de alteraciones del sistema nervioso central en preeclámpticas severas durante el puerperio, ya que tanto el edema cerebral como la eclampsia posparto, que están íntimamente relacionados con la perfusión cerebral 23,24 , podrían evitarse con la disminución del líquido intravascular y del tono venoso periférico 25,26 . Los riesgos del tratamiento con diuréticos posparto son escasos y se ha comprobado que disminuyen aún más con el uso de suplemento de potasio oral 21 .…”
Section: Discussionunclassified